Biochar ageing in polluted soils and trace elements immobilisation in a 2-year field experiment. (1st December 2021) - Campos, Paloma; Knicker, Heike; Miller, Ana Z.; Velasco-Molina, Marta; De la Rosa, José María
Abstract: Biochar application to soils has become a focus of research during the last decade due to its high potential for C sequestration. Nevertheless, there is no exhaustive information on the long-term effects of biochar application in soils contaminated with trace elements. In this work, a 2-year field experiment was conducted comprising the application of different types of biochar to acidic and moderately acidic soils with high concentrations of As, Cu, Pb, Ba and Zn. In addition, representative samples of each biochar were buried in permeable bags that allowed the flow of water and microorganisms but not their physical interaction with soil aggregates. The biochars significantly adsorbed trace elements from polluted soils. However, given the high total concentration of these persistent trace elements in the soils, the application of biochars did not succeed in reducing the concentration of available metals (CaCl2 extractable fraction). After 2 years of ageing under field conditions, some degradation of the biochars from olive pit, rice husk and wood were observed. This study provides novel information concerning the biochar alterations during ageing in polluted soils, as the decrease of aryl C signal observed by 13 C nuclear magnetic resonance (NMR) spectroscopy and the presence of O-containing groups shown by Fourier Transform mid-Infrared Spectroscopy (FT-IR) in aged biochar which enhanced trace elements adsorption. Scanning electron microscopy (SEM) revealed slight changes on surface morphology of aged biochar particles. Graphical abstract: Image 1 Highlights: Metal immobilisation by biochar was determined by burying and used as amendment. Field-aged biochars exhibited significant adsorption of trace element contents. > 8 t ha −1 of biochar are needed to reduce soil-available trace element contents. Biochar amendment increased total C and aryl C in soils at 0–10 cm depth. Biochar aromatic C was degraded under 2-year field ageing.